EVALUASI KEBIJAKAN PELAYANAN KELUARGA BERENCANA PADA DINAS PENGENDALIAN PENDUDUK DAN KELUARGA BERENCANA KABUPATEN DONGGALA - Novita; Nurhannis; M. Nur Alamsyah (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2024)
The research aims to understand and analyze the family planning (FP) service policy at the Population and Family Planning Agency of Donggala District; the research uses a Qualitative Descriptive approach; Determination of Informants through purposive sampling; Data collection includes observation, interviews, documentation; Data analysis is an interactive model, namely data condensation and presentation, and drawing conclusions. The research findings are as follows: (1) Effectiveness, the time taken for FP service procedures is not conducted promptly; (2) Efficiency, the use of contraceptives by Family Planning Service users is dominated by short-acting contraceptives such as injections and pills; (3) Sufficiency, the delivery of information by FP service policy implementers regarding contraceptives to users is still very inadequate; (4) Equity, FP service policy has not been implemented evenly; (5) Responsiveness, the Population and Family Planning Agency of Donggala District as the implementer of FP service policy has a good response; (6) Appropriateness, the FP service policy implemented by the Population and Family Planning Agency of Donggala District for users is appropriate. It is hoped that the Population and Family Planning Agency of Donggala District will develop standard FP service time; and be able to minimize the side effects of contraceptive use; Policy implementers provide clear and complete information about follow-up times, benefits, advantages, disadvantages, and side effects of contraceptive use; and provide procedural justice, namely follow-up examinations post-procedure to identify complaints or side effects caused by contraceptive use.